An update on clinical biochemical RIs of rabbits with special consideration for age, gender, and size. (5th March 2018) - Korn, Anne K.; Bauer, Natali; Moritz, Andreas; Erhardt, Georg
Abstract : Background: Literature regarding the impact of age and breed size on clinical biochemical measurands in rabbits is scarce. Objectives: We aimed to establish clinical biochemical measurand RIs for rabbits bred and kept under standard conditions and to evaluate the impact of gender, age, and breed size on the results using a Nova CRT8 analyzer (Nova Biomedical GmbH) and an ABX Pentra 400 analyzer (ABX Horiba, Axonlab). Methods: Serum samples were available from 122 adult rabbits (56 males, 66 females) of 10 different breeds and crossbreds with a mean age of 264 ± 21 days. The impact of age was evaluated by sampling 48 rabbits at weaning (8 weeks of age) and when they reached adulthood. Results: Significantly higher median values were obtained for ALT, glutamate dehydrogenase (GLDH), and potassium in adult males compared with adult female rabbits. Total bilirubin, cholesterol, creatinine, and urea were significantly higher in adult females than adult males. Juvenile animals at weaning revealed significantly higher median values for ALP, cholesterol, GGT, GLDH, glucose, phosphate, and triglycerides compared with their adulthood values. In contrast, lower median albumin, ALT, chloride, creatinine, globulin, ionized calcium, magnesium, potassium, total protein, urea, and calcium‐phosphate ratios were seen at the time of weaning compared with adulthood values. Significantly lower median CK, creatinine, and ALT were found in dwarf/small rabbit breeds compared with intermediate/large breeds. Conclusions: These RIs are especially useful for rabbit production and experimental studies. Age should be considered when evaluating clinical biochemical measurands. Creatinine, CK, and ALT are affected by organ mass.